Burundi : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility highlights economic developments and fiscal policy. The political transition process has advanced significantly in 2005, and further progress has been made in securing peace. Burundi's external debt is unsustainable even after the full use of traditional debt relief mechanisms. Burundi will thus require substantial debt relief under the enhanced HIPC Initiative as described in the decision point document. Possible setbacks in the political and security situation could complicate the implementation of the program.